2001
DOI: 10.1046/j.1365-2559.2001.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between Epstein–Barr virus infection in gastric carcinomas and the expression of apoptosis‐associated proteins

Abstract: The p53 and c-myc expression patterns indicate that EBV-infected gastric carcinomas are less likely to have a natural regression via apoptosis at an early stage and explain, in part, the resistance to treatment of late stage of gastric cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
(57 reference statements)
2
14
0
2
Order By: Relevance
“…EBV infection is seen in about 10% of gastric adenocarcinoma cases [49,58,67] . Ishii et al [49] found MYC expression in early stages of EBV-positive GC was higher than that of EBV-negative GC, while MYC expression in advanced stages of EBV-positive GC was lower than that of EBV-negative tumors.…”
Section: Myc and Gastric Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…EBV infection is seen in about 10% of gastric adenocarcinoma cases [49,58,67] . Ishii et al [49] found MYC expression in early stages of EBV-positive GC was higher than that of EBV-negative GC, while MYC expression in advanced stages of EBV-positive GC was lower than that of EBV-negative tumors.…”
Section: Myc and Gastric Carcinogenesismentioning
confidence: 99%
“…EBV infection is seen in about 10% of gastric adenocarcinoma cases [49,58,67] . Ishii et al [49] found MYC expression in early stages of EBV-positive GC was higher than that of EBV-negative GC, while MYC expression in advanced stages of EBV-positive GC was lower than that of EBV-negative tumors. It was inferred that EBV might cause the host cell to induce MYC expression in early cancer development, but then negatively affect MYC expression in advanced stages of cancers, making them less likely to have a natural regression via apoptosis.…”
Section: Myc and Gastric Carcinogenesismentioning
confidence: 99%
“…However, there are some regional differences in the frequency of EBV-positive gastric carcinoma. Countries with higher values include Japan (19.3%), Germany (18%) and United States (12-16%) (18,22,40,47). Two studies conducted in Brazil demonstrated intermediate values, 8% and 11.3% (27,33).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have shown that MYC amplification or overexpression is observed in early GC patients when tumor invasion is confined to the mucosa or submucosa, regardless of the presence of lymph node metastasis (2,1822). In the study by Onoda et al (20), MYC expression was found to be more frequent and stronger in early lesions compared with advanced lesions, and Ishii et al (21) also documented increased MYC expression in early GCs in comparison with decreased MYC expression in late-stage GCs. Based on these findings and the data from the present study, MYC genetic aberrations may be an early event in the pathogenesis of gastric carcinogenesis, and the detection of MYC locus amplification could be used as an auxiliary tool in GC diagnosis and as a predictor of GC aggressiveness (22).…”
Section: Discussionmentioning
confidence: 93%